Parametric instabilities excited by ECR-resonance heating in a mirror machine - Ivanov, A.A.; Meyer, D.; Serebrennikov, K.S.; Wiesemann, K.; Wolters, U. (Вопросы атомной науки и техники, 2000)
The process of phase randomization during electron cyclotron resonance heating has been studied intensely in different aspects with single particle approximations. Studies of parametric instabilities in plasmas introduce another system of interacting oscillators, namely plasma waves. The appearance of collective motion implies a different mechanism of phase randomization with time scales close to the inverse growth rate of the modulational instability shorter than the electron bounce frequency in the mirror trap. Systematic experiments on ECR-heating show the presence of both a spectral broadening of the pump wave as well as low frequency noise close to the lower hybrid frequency, which roughly corresponds to the growth rate of the instability. The necessity of considering potential noise, the plasma eigenmodes respectively, possibly leads to a change of the existing model of phase randomization based on the single particle motion.